The impact of bedside wipes in multi-patient rooms: a prospective, crossover trial evaluating infections and survival. (April 2023) - Dadon, M.; Chedid, K.; Martin, E.T.; Shaul, I.; Greiver, O.; Katz, I.; Saadon, H.; Alfaro, M.; Hod, L.; Shorbaje, A.; Braslavsky-Siag, A.; Moscovici, S.; et al.
Summary: Background: Multidrug-resistant organisms (MDROs) are prevalent on high-touch surfaces in multi-patient rooms. Aim: To quantify the impact of hanging single-use cleaning/disinfecting wipes next to each bed. Pre-specified outcomes were: (1) hospital-acquired infections (HAIs), (2) cleaning frequency, (3) MDRO room contamination, (4) new MDRO acquisitions, and (5) mortality. Methods: Clustered randomized crossover trial at Shamir Medical Center, Israel (October 2016 to January 2018). Clusters were randomly assigned to use for cleaning either single-use quaternary ammonium wipes (Clinell) or standard practices (reusable cloths and buckets with bleach). Six-month intervention periods were implemented in alternating sequence, separated by a washout period. Five high-touch surfaces were monitored by fluorescent markers. Study outcomes were compared between periods using generalized estimating equations, Poisson regression, and Cox proportional hazards models. Findings: Overall, 7725 patients were included (47, 670 person-days), 3793 patients in rooms with intervention cleaning and 3932 patients in rooms with standard practices. During the intervention, there was no significant difference in HAI rates (incidence rate ratio: 1.6; 95% confidence interval (CI): 0.7–3.5; P = 0.3). However, in intervention rooms, the frequency of environmental cleaning was higher (odds ratio: 3.73; 95% CI: 2.0–7.1; P < 0.0001), MDRO environmental contamination rate was insignificantly lower (odds ratio: 0.7; 95% CI: 0.5–1.0; P = 0.06), new MDRO acquisition rate was lower (hazard ratio: 0.4; 95% CI: 0.2–1.0; P = 0.04), and in-hospital mortality rate was lower (incidence rate ratio: 0.8; 95% CI: 0.7–1.0; P = 0.03). Conclusion: Hanging single-use cleaning/disinfecting wipes next to each bed did not affect the HAI rates but did improve the frequency of cleaning, reduce MDRO environmental contamination, and was associated with reduced incidence of new MDRO acquisitions and reduced mortality. This is a feasible, recommended practice to improve patient outcomes in multi-patient rooms.